2019
DOI: 10.1038/s41467-019-11933-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid metabolic shifts occur during the transition between hunger and satiety in Drosophila melanogaster

Abstract: Metabolites are active controllers of cellular physiology, but their role in complex behaviors is less clear. Here we report metabolic changes that occur during the transition between hunger and satiety in Drosophila melanogaster . To analyze these data in the context of fruit fly metabolic networks, we developed Flyscape, an open-access tool. We show that in response to eating, metabolic profiles change in quick, but distinct ways in the heads and bodies. Consumption of a high sugar die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 67 publications
2
38
0
1
Order By: Relevance
“…Recent work in invertebrates, rodents, and zebrafish have increased our mechanistic understanding of the roles of metabolism in cell cycle, tissue growth, and aging (7)(8)(9)(10). Other studies have characterized metabolic responses to environmental and intrinsic challenges, such as diet and disease (11,12). Given that cellular metabolism is highly conserved, profiles in these studies have confirmed signatures of disease progression, characterized drug responses, and identified novel metabolites and pathways for future exploration (13).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in invertebrates, rodents, and zebrafish have increased our mechanistic understanding of the roles of metabolism in cell cycle, tissue growth, and aging (7)(8)(9)(10). Other studies have characterized metabolic responses to environmental and intrinsic challenges, such as diet and disease (11,12). Given that cellular metabolism is highly conserved, profiles in these studies have confirmed signatures of disease progression, characterized drug responses, and identified novel metabolites and pathways for future exploration (13).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit fly Drosophila melanogaster is a useful model organism for investigating the genetic underpinnings of motivational behaviors, owing to variety of tools for neuro-genetic manipulations, together with the fact that flies exhibit several forms of behaviors that are shaped by motivation 29,[31][32][33][34][35][36][37][38][39][40][41] . One of the systems that encodes internal states and dictates motivational drives, and consequently, behavioral choices in Drosophila is the Neuropeptide F/Neuropeptide F receptor [42][43][44][45][46][47][48][49][50][51][52][53][54] .…”
Section: Introductionmentioning
confidence: 99%
“…O consumo de uma dieta rica em açúcar diminui as diferenças metabólicas e comportamentais entre os estados jejum e alimentado, e remodela a forma como os nutrientes são utilizados na alimentação (WILINSKI et al 2019). Além disso, o excesso de açúcar na dieta inibe o fator de transcrição dFOXO (DOBSON et al, 2016), que controla o envelhecimento em Drosophila melanogaster (HWANGBO et al, 2004) e é crucial para regular alterações transcricionais desenvolvidas no tempo de vida da mosca.…”
Section: Longevidadeunclassified